Calcium and Signal Transduction 2018
DOI: 10.5772/intechopen.80811
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Calcium Signaling Pathways in Breast Cancer

Abstract: Breast cancer is the second most common cancer in women and the fifth cause contributing to death due to the cancer condition. It is essential to deeply understand the complex cellular mechanisms leading to this disease. There are multiple connections between calcium homeostasis alterations and breast cancer in the literature, but no consensus links the mechanism to the disease prognosis. Among the cells contributing to the breast cancer are the breast telocytes, which connect through gap junctions to other ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 134 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…40 Numerous studies described the involvement of calcium signaling and transport in tumorigenesis 41 and specifically in BC. 42 It is not clear how deregulation of calcium homeostasis might induce mutations; however, growing evidence suggest that calcium bears modulating effects upon the DNA repair activities of proteins such as RAD51, 43 AMPK, 44 EXO1, 45 and Ku80. 46 Moreover, Notch receptors are calcium-dependent 47 and Notch1 itself was detected as a regulator of DNA damage response in leukemia 48 ; in BC, Notch signaling pathway is known to be aberrantly activated, 49 and finally Notch1 was reported to actuate ER-dependent transcription in ER+ BC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Numerous studies described the involvement of calcium signaling and transport in tumorigenesis 41 and specifically in BC. 42 It is not clear how deregulation of calcium homeostasis might induce mutations; however, growing evidence suggest that calcium bears modulating effects upon the DNA repair activities of proteins such as RAD51, 43 AMPK, 44 EXO1, 45 and Ku80. 46 Moreover, Notch receptors are calcium-dependent 47 and Notch1 itself was detected as a regulator of DNA damage response in leukemia 48 ; in BC, Notch signaling pathway is known to be aberrantly activated, 49 and finally Notch1 was reported to actuate ER-dependent transcription in ER+ BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of evidence supports the role of estrogen as a regulator of calcium absorption and reabsorption 40 . Numerous studies described the involvement of calcium signaling and transport in tumorigenesis 41 and specifically in BC 42 . It is not clear how deregulation of calcium homeostasis might induce mutations; however, growing evidence suggest that calcium bears modulating effects upon the DNA repair activities of proteins such as RAD51, 43 AMPK, 44 EXO1, 45 and Ku80 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that Ca 2+ plays a crucial role not only in malignant proliferation but also in cancer metastasis [ 55 , 56 , 57 , 58 , 59 , 60 ]. Breast cancer is considered a metastatic cancer due to its aggressive features [ 61 ].…”
Section: Introductionmentioning
confidence: 99%